2019
DOI: 10.1007/s00167-019-05696-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors are associated with return to pre-injury levels of sport and physical activity after ACL reconstruction

Abstract: Purpose The impetus of anterior cruciate ligament reconstruction (ACLR) is to allow patients to return to sport and to remain engaged in physical activity. Many patients exhibit deficits in psychological domains of health‐related quality of life which may impede return to sport and physical activity participation. Therefore, the purpose of this study was to examine the association of patient‐based, specifically psychological, and functional outcomes with return to sport and physical activity. Methods Forty par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 26 publications
2
90
0
1
Order By: Relevance
“…26 Whereas not a direct measure of physical activity intensity among individuals with ACLR, daily step count is a clinically feasible measure that is strongly related to time engaged in moderate to vigorous physical activity in this population. 7 In our study, the ACLR group took fewer steps per day than did the control group (8422 6 2663 steps per day versus 10 033 6 3046 steps per day), and the differences in step counts were similar to those described by Bell et al 7 (8158 6 2780 steps per day versus 9769 6 2785 steps per day) and Baez et al 28 (7754 6 2399 steps per day versus 9199 6 2385 steps per day) among similar populations. We are the first to identify that, in addition to diminished daily step counts, the ACLR group also displayed less average minute-level cadence at high step rates than the control group (Figure).…”
Section: Discussionsupporting
confidence: 87%
“…26 Whereas not a direct measure of physical activity intensity among individuals with ACLR, daily step count is a clinically feasible measure that is strongly related to time engaged in moderate to vigorous physical activity in this population. 7 In our study, the ACLR group took fewer steps per day than did the control group (8422 6 2663 steps per day versus 10 033 6 3046 steps per day), and the differences in step counts were similar to those described by Bell et al 7 (8158 6 2780 steps per day versus 9769 6 2785 steps per day) and Baez et al 28 (7754 6 2399 steps per day versus 9199 6 2385 steps per day) among similar populations. We are the first to identify that, in addition to diminished daily step counts, the ACLR group also displayed less average minute-level cadence at high step rates than the control group (Figure).…”
Section: Discussionsupporting
confidence: 87%
“…Baez et al reported that injury-related fear was associated with RTS and physical activity levels after ACLR. 22 ) Hartigan et al reported that kinesiophobia before surgery was lower in potential copers than in non-copers, but kinesiophobia before surgery was higher than that after surgery in both groups. 23 ) Although we did not investigate psychological factors, psychological evaluations should be conducted in future studies.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has shown that the level of kinesiophobia is higher and level of knee activity selfefficacy is lower in patients that do not return to sport following ACL reconstruction. 18,[32][33][34] In addition, the intensity of fear is highest for activities and situations that are specific to each patient. 26 Kinesiophobia, or pain-related fear of movement/reinjury, was assessed with the 11-item Tampa Scale for Kinesiophobia (TSK-11).…”
Section: Psychological Measuresmentioning
confidence: 99%